OPTIMIZATION OF THE ROLE OF THE VILLAGE CONSULTATIONAL BODY IN THE VILLAGE GOVERNMENT SYSTEM REVIEWED FROM THE PRINCIPLE OF CHECK AND BALANCE - Sihombing, Rizky Darmawansyah (NOMOI Law Review, 2024)
The implementation of village government is not only absolutely carried out by the village head, but there is a role for the Village Consultative Body in running the village government system. The Village Consultative Body, which is the representative of the village community, has the authority granted directly by Law No. 6 of 2014 concerning Villages. Furthermore, the village consultative body is also commonly known as the legislature within the scope of village government. So that on this basis, in running government in the village, the principle of checks and balances should be implemented. so that BPD can play a preventive role in potential abuse of power at the village level. This research also uses normative legal research and a statutory approach. So this research aims to find out the extent to which the law regulates village consultative bodies and also the application of the principle of check and balance in the administration of village government. In fact, the existence of the Village Consultative Body is recognized as stated in Law No. 6 of 2014 concerning Villages. So BPD is a constitutional institution in the constitutional system in Indonesia. Furthermore, the implementation of checks and balances in the village government environment should be able to occur. Considering the role and function of the village Consultative Body which includes a controlling function for the administration of government at the village level.